Pengaruh Tax Avoidance, Ukuran Perusahaan, dan Debt to Equity Ratio Terhadap Cost of Debt pada Perusahaan Manufaktur Sebsektor Aneka Industri yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024 - Puput Aprilia Sinaran; Rihfenti Ernayani; Butet Wulan Trifina (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study aims to determine the effect of tax avoidance, company size, and the debt-to-equity ratio on the cost of debt in manufacturing companies in the miscellaneous industry subsector listed on the Indonesia Stock Exchange for the period 2022–2024. The sampling technique used purposive sampling with secondary data in the form of the companies' annual financial reports. Data analysis was performed using descriptive statistical tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing using SPSS 25.The results indicate that tax avoidance and the debt-to-equity ratio influence the cost of debt, while company size does not.